THE INFLUENCE OF LEADERSHIP ON EMPLOYEE PERFORMANCE IN BANDUNG CITY SUB-DISTRICT - Gina Sofia Rahman; Suci Larassati Anjani (Journal of Public Administration, 2022)
Leadership is a process carried out by a leader or chairman in influencing others. Jobs that are influenced by one's leadership style will affect the results of employee performance in an organization. Leaders must have principles in their leadership, such as idealized influence, inspirational motivation, intellectual stimulation, individualized consideration. Therefore, the leadership carried out will affect the performance of existing employees in government. The better the function of a leadership that is carried out, it will have a positive effect on employee performance. Therefore, the influence of the quality of employee performance can occur according to the leadership management carried out on employees. This research was conducted using descriptive analysis and verification with a quantitative approach. In this study there are two variables, namely the variable leadership style (X) and the effect on employee performance (Y). The results of the data are presented using a Likert scale from the results of the questionnaire respondents with 60 employees and processed through descriptive data analysis techniques. The hypothesis to be tested in this study relates to whether or not there is a significant influence between the independent or independent variables on the dependent or independent variables. The results of the study obtained that there is an influence of leadership on employee performance in the Di District Office, Bandung City, is acceptable because it is supported by facts from the field.